IMPLEMENTATION OF FAMILY HOPE PROGRAM (PKH) IN IMPROVING COMMUNITY WELFARE IN SUKAHAJI DISTRICT, MAJALENGKA REGENCY - Diding Bajuri; Dwi Laksmi Ayu Wulandari; Galur Gumelar Tito; Faisal Fajar Putranto; Aceng Sunanto; Pipih Napipah; Pipit Fitriana (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2026)
Abstract. The Family Hope Program (PKH) is one of Indonesia’s main social protection programs aimed at reducing poverty and improving access to education, health, and social welfare services for poor households. This study aims to analyze the implementation of PKH in Sukahaji District, Majalengka Regency, by examining policy implementation indicators, external influencing factors, and the role of local government in supporting program effectiveness. This research employed a qualitative descriptive case study approach based on the policy implementation frameworks of Sabatier and Mazmanian and Grindle. Data were collected through interviews, observation, and documentation involving ten informants consisting of seven PKH facilitators, one district coordinator, one sub-district head, and one beneficiary family. Data were analyzed through data reduction, data display, and conclusion drawing, while validity was ensured through source and method triangulation. The findings reveal that PKH implementation has generally followed established guidelines and contributed to reducing the economic burden of beneficiary families as well as increasing access to education and health services. However, several challenges remain, including inconsistencies in DTKS data, delays in beneficiary data updating, limited public understanding of program provisions, and constraints in human resources and inter-institutional coordination. In addition, local socioeconomic conditions and the level of local government involvement significantly influence program effectiveness. These findings indicate that successful policy implementation depends not only on policy design but also on implementation capacity and contextual factors. Strengthening data management, socialization strategies, and stakeholder coordination is therefore essential to improve the sustainability and effectiveness of PKH implementation. Keyword: Policy Implementation; PKH; Poverty; Social Welfare. Abstrak. Program Keluarga Harapan (PKH) merupakan salah satu program perlindungan sosial pemerintah Indonesia yang bertujuan mengurangi kemiskinan serta meningkatkan akses masyarakat miskin terhadap layanan pendidikan, kesehatan, dan kesejahteraan sosial. Penelitian ini bertujuan menganalisis implementasi PKH di Kecamatan Sukahaji Kabupaten Majalengka dengan mengkaji indikator implementasi kebijakan, faktor eksternal yang memengaruhi pelaksanaan program, serta peran pemerintah daerah dalam mendukung efektivitas program. Penelitian menggunakan pendekatan studi kasus deskriptif kualitatif dengan landasan teori implementasi kebijakan Sabatier dan Mazmanian serta Grindle. Data dikumpulkan melalui wawancara, observasi, dan dokumentasi terhadap sepuluh informan yang terdiri atas tujuh pendamping PKH, satu koordinator kabupaten, satu camat, dan satu keluarga penerima manfaat. Analisis data dilakukan melalui reduksi data, penyajian data, dan penarikan kesimpulan dengan uji keabsahan menggunakan triangulasi sumber dan metode. Hasil penelitian menunjukkan bahwa implementasi PKH pada umumnya telah berjalan sesuai pedoman dan memberikan kontribusi dalam mengurangi beban ekonomi keluarga penerima manfaat serta meningkatkan akses pendidikan dan kesehatan. Namun demikian, masih ditemukan beberapa kendala, seperti ketidaksesuaian data DTKS, lambatnya pemutakhiran data penerima manfaat, rendahnya pemahaman masyarakat terhadap ketentuan program, serta keterbatasan sumber daya manusia dan koordinasi antarinstansi. Selain itu, kondisi sosial ekonomi masyarakat dan tingkat keterlibatan pemerintah daerah turut memengaruhi efektivitas pelaksanaan program. Temuan ini menunjukkan bahwa keberhasilan implementasi kebijakan tidak hanya ditentukan oleh desain kebijakan, tetapi juga oleh kapasitas pelaksana dan faktor kontekstual di tingkat lokal. Oleh karena itu, diperlukan penguatan pengelolaan data, strategi sosialisasi, dan koordinasi antarpemangku kepentingan untuk meningkatkan efektivitas dan keberlanjutan program. Kata Kunci: Implementasi Kebijakan; PKH; Kemiskinan; Kesejahteraan.